Tomás González: de la desesperanza, la derrota y otras muertes circulares - Bermúdez, Ronald (Pontificia Universidad Católica del Perú, 2025)
In response to the question “Why are death and violence determining factors in Colombian literary creation?”, this paper seeks to argue the level of coherence in resistant positions that circulate less massively and advocate for ways of perceiving and representing reality that differ from those already institutionalized by the literary industry. The analysis examines four novels by Colombian writer Tomás González (1983, 2000, 2003, 2010), embedded in aesthetic dialogues that define the state of the art of national literature. The conclusion drawn is that the author's narrative not only recreates the dialectic between literary creation and the total collapse of the social universe in which death and violence are represented, but also creates new spaces of meaning.

En respuesta a la pregunta “¿por qué la muerte y la violencia son determinantes en la creación literaria colombiana?”, este trabajo busca argumentar el grado de coherencia en posiciones resistentes que circulan de manera menos masiva, y que apuestan por formas diferentes de percibir y repre-sentar la realidad a las ya institucionalizadas desde la industria literaria. El análisis pone en perspectiva cuatro novelas del escritor colombiano Tomás González (1983, 2000, 2003, 2010) inscritas en diálogos estéticos que determinan el estado del arte de la literatura nacional. Se concluye que la narrativa del autor no solo recrea la dialéctica entre creación literaria y el colapso total del universo social en que muerte y violencia son representadas, sino que también crea nuevos espacios de significación.
Tomás González: on Despair, Defeat and Other Deaths
Keywords: Tomás González; Hispanic American literature; Colombian novel; Narratives of violence; Death and poetics; Tomás González; Literatura hispanoamericana; Novela colombiana; Narrativa de la violencia; Poética y muerte; https://purl.org/pe-repo/ocde/ford#6.02.06